2018
DOI: 10.1186/s13568-018-0629-9
|View full text |Cite
|
Sign up to set email alerts
|

The influence of in vitro pectin fermentation on the human fecal microbiome

Abstract: Pectin is a complex dietary fiber and a prebiotic. To investigate pectin-induced changes in the gut microbiome and their effects on the short chain fatty acids (SCFAs) production, we performed in vitro pectin fermentation using the feces of three Korean donors. The pectin degradations in all three donors were observed. While the donors displayed differences in baseline gut microbiota composition, commonly increased bacteria after pectin fermentation included Lachnospira, Dorea, Clostridium, and Sutterella. Reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
62
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(70 citation statements)
references
References 49 publications
8
62
0
Order By: Relevance
“…Dialister , for example, was found in higher abundance linked to consumption of dietary fiber from whole-grain or soluble corn fiber (47). Sutterellaceae was increased in in vitro citrus pectin fermentation (45). Bilophila , a bile-tolerant micro-organism, was found in increased abundance associated with consumption of an animal-based diet and milk fat (18, 48).…”
Section: Discussionmentioning
confidence: 99%
“…Dialister , for example, was found in higher abundance linked to consumption of dietary fiber from whole-grain or soluble corn fiber (47). Sutterellaceae was increased in in vitro citrus pectin fermentation (45). Bilophila , a bile-tolerant micro-organism, was found in increased abundance associated with consumption of an animal-based diet and milk fat (18, 48).…”
Section: Discussionmentioning
confidence: 99%
“…At the genus level, Bacteroides , Lachnospira , Streptococcus and Klebsiella were the dominant bacteria in the BHI group in LEfse analysis. Bacteroides is one of the most abundant genera in the gut and has a positive correlation with propionic acid production (Nakano et al 2013), and Lachnospira also plays an important role in SCFA production (Bang et al 2018). Previous studies have reported that Streptococcus and Klebsiella were widely distributed in the human skin, mouth and intestine, and Streptococcus can degrade digested proteins into peptides in human gut (Macfarlane et al 1988; Sekirov et al 2010; Brisse et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The most extensively studied fruit fiber prebiotic component is pectin, which comprises on average 35% of fruit fiber cell wall content [9,37]. A Korean in vitro human colonic microbiota model system study (3 male donors with diverse microbiota profiles) confirmed the effectiveness of pectin in promoting robust prebiotic activity in all subjects [39]. Although donors had differences in baseline colonic microbiota composition, there were similar increases in healthy bacteria after pectin fermentation including species belonging to butyrate producing Clostridium cluster XIV (e.g., Lachnospira ), and Sutterella .…”
Section: Fruit As a Prebiotic Sourcementioning
confidence: 99%